Developmental functions for the Caenorhabditis elegans Sp protein SPTF-3 - Sleiman, Sama F. (2011)
Sp factors are important for animal development and the transcriptional regulation of a wide variety of genes. How they influence the developmental decisions of individual cells within the organism, however, is poorly understood. To better understand the developmental functions for Sp transcription factors, we have characterized the functions of Caenorhabditis elegans SPTF-3 using RNAi knockdown and a non-null, hypomorphic mutant allele. We find that disruption of sptf-3 confers a variety of developmental defects, including defects in development of the egg-laying system, oocyte production, and embryonic morphogenesis. sptf-3 mutants exhibit defects in vulval lineage polarity, a phenotype previously only observed in mutants defective in Wnt signaling. We show that the embryonic function of sptf-3 is dependent on germline activity, arguing that the gene has an important maternal contribution to embryonic development. An evaluation of reporter gene expression suggests that SPTF-3 exhibits specificity, in that it can influence the expression of a given gene in some cells but not others, and that SPTF-3 participates in the maintenance of gene expression states in differentiated cells. We propose SPTF-3 provides a good model to study the in vivo functions for Sp transcription factors during animal development.